Torture and deprivation of freedom: the Spanish case - Ubasart, Gemma (Crime, law and social change, 2013)
In 2004 Theo van Boven, as Special Rapporteur of the United Nations, alerted the world community that torture and ill-treatment were more than sporadic practices within Spain. Numerous studies carried out by human rights organizations and international institutions endorse this affirmation. This paper attempts to analyse the elements that facilitate cases of torture and ill-treatment while proposing ideas about how to orient political action to eradicate these practices. Situated in the discipline of public policy this paper will try to understand the deprivation of freedom focusing the analysis on the most extreme practices of the State violation of human rights that are produced in these areas. This article first addresses a quantitative description of the presence of torture in Spain. The second section details the historical and political specificities of the Spanish case that are useful in order to understand the question and at the same time in order to establish points of reference for the design of public policy. In the third section the elements that make possible the existence of cases of torture in Spain are analysed, elaborating a typology of static and dynamic elements. The fourth section explains the relationship between democratic culture and torture.